Pregnancy Following Liver Transplantation: Review of Outcomes and Recommendations for Management - Kuljit S Parhar; Paul S Gibson; Carla S Coffin (Canadian Journal of Gastroenterology)
Liver transplantation is considered to be the treatment of choice for end-stage liver disease and its success has led to an increase in the number of female liver transplant recipients who are of childbearing age. Several key issues that are noted when counselling patients who are considering pregnancy following liver transplantation include the optimal timing of pregnancy, optimal contraception methods and the management of immunosuppression during pregnancy. The present review summarizes the most recent literature so that the clinician may address these issues with their patient and enable them to make informed decisions about pregnancy planning. The authors review recent studies examining maternal and fetal outcomes, and the rates of complications including risk of graft rejection. Subsequently, the authors provide recommendations for counselling prospective mothers and the management of the pregnant liver transplant recipient.